ETHYLENE RESPONSE FACTOR 96 positively regulates Arabidopsis resistance to necrotrophic pathogens by direct binding to GCC elements of jasmonate – and ethylene‐responsive defence genes. (3rd July 2015) - Catinot, Jérémy; Huang, Jing‐Bo; Huang, Pin‐Yao; Tseng, Min‐Yuan; Chen, Ying‐Lan; Gu, Shin‐Yuan; Lo, Wan‐Sheng; Wang, Long‐Chi; Chen, Yet‐Ran; Zimmerli, Laurent
Abstract: The ERF (ethylene responsive factor) family is composed of transcription factors (TFs) that are critical for appropriate A rabidopsis thaliana responses to biotic and abiotic stresses. Here we identified and characterized a member of the ERF TF group IX, namely ERF96, that when overexpressed enhances A rabidopsis resistance to necrotrophic pathogens such as the fungus B otrytis cinerea and the bacterium P ectobacterium carotovorum . ERF96 is jasmonate (JA) and ethylene (ET) responsive and ERF96 transcripts accumulation was abolished in JA‐insensitive coi1‐16 and in ET‐insensitive ein2‐1 mutants. Protoplast transactivation and electrophoresis mobility shift analyses revealed that ERF96 is an activator of transcription that binds to GCC elements. In addition, ERF96 mainly localized to the nucleus. Microarray analysis coupled to chromatin immunoprecipitation‐PCR of A rabidopsis overexpressing ERF96 revealed that ERF96 enhances the expression of the JA/ET defence genes PDF1.2a, PR ‐3 and PR ‐4 as well as the TF ORA59 by direct binding to GCC elements present in their promoters. While ERF96 ‐RNAi plants demonstrated wild‐type resistance to necrotrophic pathogens, basal PDF1.2 expression levels were reduced in ERF96 ‐silenced plants. This work revealed ERF96 as a key player of the ERF network that positively regulates the A rabidopsis resistance response to necrotrophic pathogens. Abstract : This work describes the function of the transcription factor ERF96 in A rabidopsis thaliana immunity. Over‐expression of ERF96 resulted in enhanced resistance to necrotrophic fungal and bacterial pathogens. Transcriptome and ChIP‐PCR analyses indicated that the activator of transcription ERF96 directly regulates pathogen‐responsive defence genes and the transcription factor ORA59. These findings revealed ERF96 as a novel modulator of the Arabidopsis immunity network.